Gender and ethnic wage gaps in Guatemala from a matching comparisons perspective - Hugo \~Nopo; Alberto Gonzales (Inter-American Development Bank, Research Department, 2008)
This paper analyzes gender and ethnic wage gaps in Guatemala for the period 2000-2006, applying a matching comparisons technique, finding pronounced wage gaps along both gender and ethnic dimensions, the latter being greater. Wage gaps in Guatemala are partially explained by differences in human capital characteristics, especially education, between indigenous and non-indigenous and males and females, which calls for equalization of educational opportunities for the population. However, wage gaps are greater than differences in education would predict, which suggests the need for interventions: information campaigns to generate consciousness regarding the need to provide more equal opportunities in labor markets according to each individual's productivity.
Keywords: 330; Lohndrift; Geschlecht; Ethnische Gruppe; Matching; Guatemala